Brain damage and neurological symptoms induced by T-2 toxin in rat brain - Guo, Pu; Liu, Aimei; Huang, Deyu; Wu, Qinghua; Fatima, Zainab; Tao, Yanfei; Cheng, Guyue; Wang, Xu; Yuan, Zonghui (Toxicology letters, 2018)
T-2 toxin, a trichothecene mycotoxin, is a common contaminant in food and animal feed, and is also present in processed cereal products. The most common route of T-2 toxin exposure in humans is through dietary ingestion. The cytotoxic effects of T-2 toxin include modifications to feeding behavior, nervous disorders, cardiovascular alterations, immunosuppression, and hemostatic derangements. However, to date, effects on the central nervous system (CNS) have rarely been reported. In the present study, female Wistar rat were given a single dose of T-2 toxin at 2 mg/kg b.w. and were sacrificed at one, three, and seven days post-exposure. Histopathological analysis and transmission electron microscope (TEM) observations were used to investigate injury to the brain and pituitary gland. Damage to the brain and pituitary at the molecular level was detected by real time-polymerase chain reaction (RT-PCR), western blot, and immunohistochemical assays. Liquid chromatograph-mass spectrometer/mass spectrometer (LC-MS/MS) was used to investigate T-2 concentration in the brain. The results showed that pathological lesions were obvious in the brain at three days post-exposure; lesions in the pituitary were not observed until seven days post-exposure. Autophagy in the brain and apoptosis in the pituitary suggest that T-2 toxin may induce different acute reactions in different tissues. Importantly, low concentrations of T-2 toxin in the brain were observed in only one rat. Responsible for the above mentioned, we hypothesize that brain damage caused by this toxin may be due to the ability of the toxin to directly cross the blood-brain barrier (BBB). Therefore, given its widespread pollution in food, we should pay more attention to the neurotoxic effects of the T-2 toxin, which may have widespread implications for human health.
Keywords: Animals; Microscopy, Electron, Transmission; Real-Time Polymerase Chain Reaction; apoptóza; hodnocení rizik; Female; Autophagy; neurotoxické syndromy; Rats, Wistar; Neurotoxicity Syndromes; Blotting, Western; ženské pohlaví; Apoptosis; Tandem Mass Spectrometry; T-2 Toxin; T-2 toxin; Time Factors; časové faktory; Immunohistochemistry; chování zvířat; kapilární permeabilita; Chromatography, Liquid; Blood-Brain Barrier; brain; mozek; Risk Assessment; hematoencefalická bariéra; imunohistochemie; autofagie; western blotting; regulace genové exprese; tandemová hmotnostní spektrometrie; Capillary Permeability; hypofýza; Brain; neurotoxicity; hypophysis; Behavior, Animal; Pituitary Gland; transmisní elektronová mikroskopie; zvířata; Gene Expression Regulation; human health; kvantitativní polymerázová řetězová reakce; chromatografie kapalinová; potkani Wistar